ANALISIS PENGARUH PENGHARGAAN EKSTRINSIK TERHADAP MOTIVASI KERJA (Studi pada Sebuah Distributor Panel Serat Kayu dan Lantai Kayu) - Evi Maria (Jurnal Bisnis dan Ekonomi, 2007)
People work for many reasons, and one of them is earning money. But in fact, earning money is not the only reason for this people to stay and work in that company. Based on the research, it’s found that many factors can influence the working motivation of the people. This article explains about extrinsic rewards (salary and wage, fringe benefit, interpersonal reward and promotion which influence the working motivation of the workers in a panel and wood floor distributor. The result of this research can be use for giving recommendation for the company in how to give an appropriate reward for their workers. Key words: Working Motivation, Extrinsic Rewards.